Exploring the role of nanomedicines for the therapeutic approach of central nervous system dysfunction: At a glance - Rhaman, Md. Mominur; Islam, Md. Rezaul; Akash, Shopnil; Mim, Mobasharah; Noor alam, Md.; Nepovimova, Eugenie; Valis, Martin; Kuca, Kamil; Sharma, Rohit (Frontiers in Cell and Developmental Biology, 2022)
In recent decades, research scientists, molecular biologists, and pharmacologists have placed a strong emphasis on cutting-edge nanostructured materials technologies to increase medicine delivery to the central nervous system (CNS). The application of nanoscience to the treatment of neurodegenerative diseases (NDs) like Alzheimer's disease (AD), Parkinson's disease (PD), Multiple sclerosis (MS), Huntington's disease (HD), Brain cancer, and Hemorrhage has the potential to transform care. Multiple studies have indicated that nanomaterials can be used to successfully treat CNS disorders in the case of neurodegeneration. Nanomedicine development for the cure of degenerative and inflammatory diseases of the nervous system is critical. Nanoparticles may act as a drug transporter that can precisely target sick brain sub-regions, boosting therapy success. It is important to develop strategies that can penetrate the blood brain barrier (BBB) and improve the effectiveness of medications. One of the probable tactics is the use of different nano-scale materials. These nano-based pharmaceuticals offer low toxicity, tailored delivery, high stability, and drug loading capacity. They may also increase therapeutic effectiveness. A few examples of the many different kinds and forms of nanomaterials that have been widely employed to treat neurological diseases include quantum dots, dendrimers, metallic nanoparticles, polymeric nanoparticles, carbon nanotubes, liposomes, and micelles. These unique qualities, which include sensitivity, selectivity, and the ability to traverse the BBB when employed in nano-sized particles, make these nanoparticles often used for imaging studies and the treatment of NDs. Multifunctional nanoparticles carrying pharmacological medications serve two purposes: they improve medication distribution while also enabling cell dynamics imaging and pharmacokinetic study. However, because of the potential for wide-ranging clinical implications, safety concerns persist, limiting any potential for translation. The evidence for using nanotechnology to create drug delivery systems that could pass across the BBB and deliver therapeutic chemicals to CNS was examined in this study.